267 Determining the effects of diet complexity and body weight categories on growth performance of nursery pigs - Lunedo, Raquel (J Anim Sci, 2020)
Our objective was to determine the effects of feeding complex or simple diets to nursery pigs sorted by body weight (BW) on growth performance. A total of 1,296 pigs (PIC 337×Camborough, initially 5.8±0.10 kg) were used in a 35-d study. Pens of pigs were blocked by gender and randomly allotted to 1 of 6 treatments. Treatments included three BW categories: light (4.7±0.10 kg), medium (5.8±0.10 kg), and heavy (7.1±0.10 kg); and two dietary strategies: simple (SD) or complex (CD) diets. Treatments were fed in two phases from d 0-10 and 10-20, followed by 15-d with common diet. Simple diets had greater soybean meal (20/26 vs 12/20%) and phytase levels (2,000 vs 500FTU/kg), lower specialty protein (8.1/4.2 vs 12.0/6.8%) and lactose levels (12/5.3 vs 18/11.5%) compared to CD. There were 8 or 11 pens per treatment and 24 pigs per pen. Data were analyzed using the GLIMMIX procedure of SAS with pen as the experimental unit. There was no evidence of interaction for any response criteria. During the treatment period (d 0-20), pigs fed CD had greater (P< 0.05) average daily gain (ADG), average daily feed intake (ADFI), and improved (P< 0.10) feed efficiency (G:F) compared to pigs fed SD. During the common period (d 20-35), pigs fed SD had greater (P< 0.05) ADG and ADFI compared to pigs fed CD. Overall (d 0-35), there was no evidence of differences in ADG, ADFI, G:F, and final BW between SD or CD. Heavy pigs had the greatest (P< 0.05) ADG and ADFI followed by medium and light pigs. In conclusion, pigs fed SD after weaning had poorer performance compared to pigs fed CD but were able to recover the loss in performance when switched to a common diet. This indicates nursery nutrition programs can be simplified without negatively affecting performance from 5.8 to 16.6 kg. [Image: see text]